2014
DOI: 10.1016/j.jtcvs.2014.06.093
|View full text |Cite
|
Sign up to set email alerts
|

Should early extubation be the goal for children after congenital cardiac surgery?

Abstract: Most children undergoing congenital heart surgery can be extubated in the operating room. Most neonates, including many undergoing complex procedures, can be extubated within the first 24 hours after surgery. Early extubation was associated with low morbidity rates and short lengths of intensive care unit and hospital stays.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
109
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(133 citation statements)
references
References 17 publications
9
109
1
2
Order By: Relevance
“…The little contribution of the thoracic cage to respiratory function, the relatively weak intercostal muscles, and narrower airway in these age groups were shown to be the anatomical and physiologic reasons for the risk of prolonged MV [7]. Lower body weight and failure to thrive were also risk factors for prolonged MV possibly associated with the same reasons above-mentioned [6,19,20]. Similar to previous reports, younger patient age and lower body weight were associated with prolonged MV in our study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The little contribution of the thoracic cage to respiratory function, the relatively weak intercostal muscles, and narrower airway in these age groups were shown to be the anatomical and physiologic reasons for the risk of prolonged MV [7]. Lower body weight and failure to thrive were also risk factors for prolonged MV possibly associated with the same reasons above-mentioned [6,19,20]. Similar to previous reports, younger patient age and lower body weight were associated with prolonged MV in our study.…”
Section: Discussionsupporting
confidence: 89%
“…Considering these unfavorable effects of prolonged MV, there has been a paradigm shift in the postoperative management, from slow weaning from MV to promote early extubation (EE), ambulation, and hospital discharge [5]. Although the term ''early extubation'' generally refers to tracheal extubation in the operating room or within the first 6-8 h of PICU admission, some centers extend this period up to 24 h [6]. Previous studies showed that EE results in fewer complications, shortens the length of PICU and hospital stay, is cost-effective, and is safe and possible in carefully selected patients [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] The form of the cardiac pathology, the complexity of the operation, surgical complications, the presence of residual defects, myocardial dysfunction, presence of pulmonary parenchyma, and comorbid problems may complicate extubation, thereby, increasing the length of stay on the mechanical ventilator. [2][3][4] Prolonged endotracheal intubation complicates postoperative procedures, leading to increased mortality and morbidity rates.…”
mentioning
confidence: 99%
“…Implementation of a comprehensive early 161 extubation strategy for all children with congenital heart disease is associated with low morbidity rates and short length of stay. Although there are many benefits resulting from early extubation, it is important to ensure that the practice is both successful and safe (21,22). The majority of children undergoing congenital heart surgery can be extubated in the operating room, but there is question of its benefit and drawback in comparison with extubation couple hours after operation.…”
mentioning
confidence: 99%